Presenting in English - How to Give Successful Presentations - Mark Powell (United Kingdom Cengage Learning EMEA, 2002)
Resulting from research into what really makes presentations so successful, this book's approach combines the language and skills needed to give effective presentations. The book is aimed at intermediate to upper intermediate students and employs simple rhetorical techniques. It shows how to deliver complicated subject matter clearly and effectively and employs models for clarifying and dealing with questions. The skills training is step-by-step and the open format allows for personalized input. An accompanying cassette is available, whose recordings are designed to improve delivery.
Keywords: English Language; Business Presentations; Public Speaking